Transcriptome and metabolome profiling unveil the accumulation of chlorogenic acid in autooctoploid Gongju - Zhao, Li; Cao, Yu; Shan, Gaomeng; Zhou, Jiayi; Li, Xintong; Liu, Peng; Wang, Yansong; An, Songhao; Gao, Ri (Frontiers in Plant Science, 2024)
Gongju is recognized as one of the four traditional Chinese medicinal herbs, and its main constituents are chlorogenic acid (CGA) and its derivative material. CGA content in autooctoploid Gongju are considerably elevated compared with those in parental tetraploid Gongju at different flowering stages. However, the underlying molecular mechanisms governing the regulation CGA content remain poorly understood.Therefore, we conducted integrated transcriptome and metabolome analyses of different flowering stages in autooctoploid and tetraploid Gongju to elucidate the underlying molecular mechanisms governing CGA biosynthesis. Transcriptome analysis showed that the number of differentially expressed genes in the budding stage (BS), early flowering stage (EF), and full flowering stage (FF) of tetraploid and octoploid Gongju were 3859, 11,211, and 6837, respectively. A total of 563, 466, and 394 differential accumulated metabolites were respectively identified between the bud stages of tetraploid and octoploid Gongju (4BS vs. 8BS), between the early flowering stages of tetraploid and octoploid Gongju (4EF vs. 8EF), and the full flowering stages of tetraploid and octoploid Gongju (4FF vs. 8FF) groups. The integrated analysis of transcriptomics and metabolomics revealed that the expression of pma6460 and mws0178, which are key enzymes involved in the CGA synthesis pathway, increased during the flowering stages of octoploid Gongju relative to that of tetraploid Gongju.CmHQT and CmC3H genes associated with CGA synthesis were higher in octoploid plants than in tetraploid plants at various flowering stages. To investigate the potential regulation of transcription factors involved in CGA synthesis, we analyzed the coexpression of CmC3H and CmHQT with CmMYBs and CmbHLHs. Results indicated that transcription factors, such as CmMYB12 (Cluster-30519.0), CmMYB26 (Cluster-75874.0), CmMYB5 (Cluster-94106.0), CmMYB1 (Cluster-71968.7), CmbHLH62 (Cluster-32024.1), CmbHLH75 (Cluster-62341.0), CmbHLH62 (Cluster-32024.8), CmbHLH75 (Cluster-60210.0), and CmbHLH16 (Cluster-90665.1) play a pivotal role in CGA synthesis regulation. The present study provides novel 3 insights into the molecular mechanisms underlying CGA accumulation in autopolyploid Gongju.